Similarities and Differences between the Pathogenesis and Pathophysiology of Diastolic and Systolic Heart Failure - Kazuo Komamura (Cardiology Research and Practice, 2013)
Pathophysiology of heart failure has been considered to be a damaged state of systolic function of the heart followed by a state of low cardiac output that is, systolic heart failure. Even if systolic function is preserved, left ventricular filling in diastole can be impeded and resulted in elevation of filling pressure and symptoms of heart failure. This kind of heart failure is called diastolic heart failure. Nowadays, diastolic heart failure is referred to as heart failure with preserved ejection fraction (HFpEF), whereas systolic heart failure is referred to as heart failure with reduced ejection fraction (HFrEF). In this paper, the similarities and differences between the pathogenesis and pathophysiology of diastolic and systolic heart failure were reviewed. Although diastolic heart failure is a common condition of heart failure worldwide, its pathophysiology has not been sufficiently elucidated. This is thought to be the most significant reason for a lack of established treatment methods for diastolic heart failure. We hope to proceed with future studies on this topic.